CONTRIBUTION A L’ETUDE DES PARASITES DES OISEAUX DE CAGE DANS LA REGION DE SOUK AHRAS - KHELAIFIA Abir; ZOUAOUI Aridj Nour elyakine (My University, 2025)
This study focuses on the investigation of external and internal parasites affecting caged birds in the Souk Ahras region, a common issue in domestic poultry farming. The study was conducted between January and April 2025, involving 40 birds of various species (Canaries, Goldfinches, Parrots, Parakeets, Nightingales, Mule bird, Gouldian finch, Linnets and Albinos) collected from several amateur and professional breeders. Ectoparasites were collected through brushing and identified morphologically, while endoparasites were detected using the fecal flotation technique. The results revealed a high prevalence of the ectoparasite Dermanyssus gallinae, and internal parasites such as Entamoeba sp., coccidia (Eimeria sp., Isospora sp.), and Toxoplasma gondii, as well as intestinal nematodes (Capillaria spp.). These parasites pose a significant threat to bird health, especially in captivity. This work highlights the importance of sanitary prevention in caged bird farming and the need to raise awareness among breeders. It also proposes practical recommendations to reduce parasitic infestations and improve the welfare of birds in captivity. --------------------------------------------------------------------------------------------------------------------------- يتناول هذا العمل دراسة الطفيليات الخارجية والداخلية التي تصيب طيور الأقفاص في منطقة سوق أهراس، وهي مشكلة شائعة في تربية الدواجن المنزلية. أنجزت الدراسة بين شهري يناير وأبريل 2025 ، وشملت 40 طائرًا من أنواع مختلفة (الكناري الحسون الببغاوات، الببغاوات الصغيرة، البلبل الهجين، الجولديان الحنون والمهق جمعت من عدة مربي طيور هواة ومحترفين. تم جمع الطفيليات الخارجية عن طريق الفحص بالفرشاة وتحليلها مورفولوجيا، في حين كشفت الطفيليات الداخلية باستخدام تقنية تعويم البراز. كشفت النتائج وجود متكرر للطفيلي الخارجي Dermanyssus gllinae" ، وكذلك الطفيليات الداخلية مثل والديدان الخيطية ،"Toxoplasma gondii "و " Isospora sp." " Eimeria sp." والكوكسيديا ،". Entamoeba sp" المعوية ".Capillaria spp". تمثل هذه الطفيليات خطرًا كبيرًا على صحة الطيور، خاصة في ظروف التربية داخل الأقفاص. يبرز هذا العمل أهمية الوقاية الصحية في تربية طيور الأقفاص وضرورة توعية المربين، ويقترح توصيات عملية للحد من الإصابات الطفيلية وتحسين رفاهية الطيور في الأسر. ------------------------------------------------------------------------------------------------------------------------- Ce travail porte sur l’étude des parasites externes et internes affectant les oiseaux de cage dans la région de Souk Ahras, un problème fréquent dans l’élevage avicole domestique. L’étude a été réalisée entre janvier et avril 2025, sur 40 oiseaux issus de diverses espèces (Canaris, Chardonnerets, Perroquets, Perruches, Rossignols, Mulet, Gould, Linottes et Albinos) et collectés auprès de plusieurs éleveurs amateurs et professionnels. Les ectoparasites ont été collectés par brossage et analysés morphologiquement, tandis que les endoparasites ont été détectés par la technique de flottaison des fientes. Les résultats ont révélé la présence fréquente d’ectoparasite «Dermanyssus gllinae», ainsi que des parasites internes comme «Entamoeba sp.», les coccidies «Eimeria sp.» «Isospora sp.» et «Toxoplasma gondii», les nématodes intestinaux «Capillaria spp.». Ces parasites représentent un risque important pour la santé des oiseaux notamment en captivité. Ce travail met en lumière l’importance de la prévention sanitaire dans l’élevage des oiseaux de cage et la sensibilisation des éleveurs, et propose des recommandations pratiques pour limiter les infestations parasitaires et améliorer le bien-être des oiseaux en captivité
Keywords: Parasites; cage birds; Souk Ahras; Algeria. الطفيليات الطيور القفصية، سوق أهراس الجزائر. : Parasites; oiseaux de cage; Algérie